Determination of MIC and NIC values of Allivum sativum methanolic extract against Aeromonas hydrophila - Ismail, Ahmad Syazwan; Shukor, Mohd Yunus; Masdor, Noor Azlina (Hibiscus Publisher, 2022)
Plant extracts have been studied extensively for their ability to suppress the growth of bacteria. Because these findings were not reported on in the benchmark values, it was not possible to compare the results of this study to other investigations. Nonlinear regression analysis of the data is one of the most accurate methods of determining this value. The minimum inhibitory concentration (MIC) and non-inhibitory concentration (NIC) values of the methanolic extract of Allium sativum against the pathogen Aeromonas hydrophila were successfully determined using Lambert and Pearson's modified Gompertz model. As shown by the model's high correlation coefficient (0.995), garlic's MIC and NIC values of 28.02 mg/mL (95% Confidence Interval from 26.42 to 29.71) and 12.60 mg/mL (95% C.I., 11.88 to 13.37) suggest that it could be used as an inhibitory agent against this essential fish pathogen.